Examination of Drinking Habits and Motives of Collegiate Student-Athletes - Elizabeth A. Taylor; Rose Marie Ward; Robin Hardin (Journal of Applied Sports Management, 2017)
Universities across the United States have reported consistently high rates of alcohol use and abuse among students during the past 20 years. The college student alcohol consumption level is considered an important public health concern. The increase in problematic drinking seems to be campus wide, but there is an understudied at-risk demographic—collegiate student-athletes. The purpose of this study is to examine student-athletes’ motives for alcohol consumption, drinking patterns, and alcohol-related negative consequences. Student-athletes (N = 283) from five Midwestern universities completed an online questionnaire assessing this behavior. Male student-athletes reported higher levels in all three categories than females. In addition, differences were found in the drinking motives of individual and team sport student-athletes. Unlike previous studies, Division I student-athletes did not differ from Division III with respect to these behaviors. Male student-athletes seem particularly at-risk for problematic alcohol consumption. Additionally, differences were found in motives experienced for alcohol consumption based on sport type (i.e., individual versus team). Level of play was not found to influence drinking motives or alcohol consumption which may signify participation in intercollegiate athletics is a greater influence than division. Differences found in gender and sport type may provide insight to help decrease dangerous drinking habits of student-athletes.
Keywords: Drinking motives; collegiate student-athletes; alcohol consumption; NCAA